2011
DOI: 10.1017/s0954102011000770
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of ancient algal mats from the McMurdo Dry Valleys, Antarctica

Abstract: Abstract:The McMurdo Dry Valleys possess a cold and dry climate which favours biomolecular preservation, and present the possibility for preservation of biological materials over long timescales. We examined patterns of bacterial DNA abundance and diversity in algal mats from 8-26 539 years of age. Bacterial DNA abundance was inferred from extractable DNA quantity and quantitative polymerase chain reaction targeting the bacterial 16S rRNA gene. Because damage to bacterial DNA could limit its availability for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…1, Table S2), the specific organisms present in a mat may vary considerably. Certain groups are regularly detected in Antarctic mats: Cyanobacteria, particularly members of the Oscillatoriales such as Leptolyngbya and Phormidium, and the Nostocales (Taton et al, 2003;Jungblut et al, 2005;Taton et al, 2006;Fernández-Valiente et al, 2007;Sutherland, 2009;Borghini et al, 2010;Verleyen et al, 2010;Anderson et al, 2011;Callejas et al, 2011;Fernandez-Carazo et al, 2011), Proteobacteria, the CFB group, Actinobacteria, and Firmicutes (Brambilla et al, 2001;Van Trappen et al, 2002;Peeters et al, 2011;Antibus et al, 2012a;Varin et al, 2012). Less commonly reported are Deinococcus-Thermus, Planctomycetes, Verrucomicrobiales, and others (Brambilla et al, 2001;Antibus et al, 2012b;Peeters et al, 2012;Varin et al, 2012).…”
Section: Microbial Mats As Microcosms Of Antarctic Lifementioning
confidence: 99%
See 1 more Smart Citation
“…1, Table S2), the specific organisms present in a mat may vary considerably. Certain groups are regularly detected in Antarctic mats: Cyanobacteria, particularly members of the Oscillatoriales such as Leptolyngbya and Phormidium, and the Nostocales (Taton et al, 2003;Jungblut et al, 2005;Taton et al, 2006;Fernández-Valiente et al, 2007;Sutherland, 2009;Borghini et al, 2010;Verleyen et al, 2010;Anderson et al, 2011;Callejas et al, 2011;Fernandez-Carazo et al, 2011), Proteobacteria, the CFB group, Actinobacteria, and Firmicutes (Brambilla et al, 2001;Van Trappen et al, 2002;Peeters et al, 2011;Antibus et al, 2012a;Varin et al, 2012). Less commonly reported are Deinococcus-Thermus, Planctomycetes, Verrucomicrobiales, and others (Brambilla et al, 2001;Antibus et al, 2012b;Peeters et al, 2012;Varin et al, 2012).…”
Section: Microbial Mats As Microcosms Of Antarctic Lifementioning
confidence: 99%
“…Nevertheless, more widespread use of molecular methods is desirable for gaining greater resolution of species composition and community diversity. The advantage provided is illustrated by the cultivation of isolates from ancient algal mats yielding 15 types of cultivable bacteria (Antibus et al, 2012b), compared to 215 operational taxonomic units (OTUs) for the same mats using clone libraries (Antibus et al, 2012a). Similarly, in studies focused only on the presence of Cyanobacteria, 16 morphotypes were identified from five mats by microscopy compared to 28 OTUs by molecular methods (Taton et al, 2006), and in a separate study of mats from the Transantarctic Mountains, six species were identified by microscopy and 15 by molecular methods (Fernandez-Carazo et al, 2011).…”
Section: Microbial Mats As Microcosms Of Antarctic Lifementioning
confidence: 99%
“…In situ primary production by mosses, lichens, terrestrial cyanobacteria and algae, including production in cryptic microbial communities that grow endolithically (literally growing in the interstitial spaces in fissured rock, where there may be more liquid water and where they are protected from the radiation and the abrasive and drying effects of the wind), is very limited (Friedmann and Ocampo, 1976; Friedmann, 1982; Schwarz et al ., 1992; Friedmann et al ., 1993; Green et al ., 1998; Kappen et al ., 1998; Pannewitz et al ., 2005; Novis et al ., 2007). However, there are several other potential sources of organic C and N to support terrestrial heterotrophs, including redistributed detritus from modern lacustrine cyanobacteria (Parker et al ., 1982; Greenfield, 1998; Elberling et al ., 2006; Hopkins et al ., 2006b; 2008a), marine detritus (Burkins et al ., 2000), and the remnants of ancient organic deposits from palaeo‐lakes, which is also believed to be of algal and cyanobacterial origin (Hall and Denton, 1995; Burkins et al ., 2000; Hall et al ., 2000; Hendy, 2000; Moorhead, 2007; Antibus et al ., 2008; Fig. S2).…”
Section: Introductionmentioning
confidence: 99%
“…Although the authors of the study could not fully exclude the possibility of colonization by soil bacteria, ancient mat samples displayed low abundance and diversity of cultivable bacteria, which would be expected due to a loss of viability over time (Antibus et al, 2012a). A paired study assessing the persistence of 16S rRNA from the same samples also found that DNA abundance and integrity declined with sample age over several millennia (Antibus et al, 2012b). Additionally, extracellular DNA has been found to comprise about 40% of the DNA in soil samples, and this relic DNA can confound the determination of microbial diversity, resulting in inflated estimates (Carini et al, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…While culturing is an important approach to studying cell survival, the vast majority of microbes have not been cultured, and may be resistant to isolation in a laboratory setting due to their as-yet unknown physiological requirements (Schloss and Handelsman, 2005). In a follow-up study of 16S rRNA gene PCR products from bulk DNA, Antibus et al (2012b) found Firmicutes, Bacteroidetes, Chloroflexi, Cyanobacteria, Actinobacteria, and Actinobacteria from the same microbial mat samples, sourced either from viable cells or preserved genetic material.…”
Section: Lake Vanda Paleomat Community Is Comprised Of Bacterial Phylamentioning
confidence: 99%